A comparative study to determine the impact of double lockdown on hospital visits, admissions, and patient outcomes in a tertiary care hospital - Showkat Hussain Tali; Andleeb Majeed; Tajali Shora; Bhat, Mohd Ashraf; Sheikh Mushtaq Ahmad (Asian Journal of Medical Sciences, 2023)
Background: Unlike COVID 19 lockdown, very little is known about the impact of non-COVID 19 lockdown and two lockdowns (post abrogation of article 370 and post COVID 19) in series on health-care delivery system. Aims and Objectives: The aim of the study was to look for the impact of two lockdowns, separately and in combination, on health-care delivery system. Materials and Methods: Data of patients visiting the pediatric outpatient department, pattern of hospital admissions and patient outcomes 1 month and 6 months before and after two lockdowns were recorded and compared within a lockdown and with each other. Results: Fall in Outpatient visits and its persistence even after 6 months was more pronounced for post COVID 19 Lockdown or lockdown 2 (–73%VS–43% and +195VS–61%). There was a statistically significant difference between admissions rates 1 month before and after lockdown 1 (post article 370 abrogation) as well as 1 month before and after lockdown 2 (P= 0.001; P< 0.0001). For the same time period, admission rates were significantly different for respiratory and gastrointestinal illnesses during the two lockdowns (<0.0001). Also, there was a significant difference between admissions rates 6 month before and after lockdown 1 and 6 months before and after lockdown 2 (P< 0.00001; P<=0.02). There was a significant difference between hospital admission rates 1 month after lockdown 1 and lockdown 2 (<0.0001). There was also significant difference between clinical spectrum of admitted patients 1 month and 6 months after the two lockdowns (<0.03–<0.0001). Conclusion: Both Lockdowns had a significant negative impact on healthcare delivery system. However, post COVID-19 lockdown had a much stronger impact.